Comorbidities, anticoagulants, and geriatric-specific physiology for the field triage of injured older adults. Issue 5 (May 2019) - Newgard, Craig D.; Lin, Amber; Eckstrom, Elizabeth; Caughey, Aaron; Malveau, Susan; Griffiths, Denise; Zive, Dana; Bulger, Eileen
Abstract : BACKGROUND: Comorbid conditions and anticoagulants have been considered as field triage criteria to raise the sensitivity for identifying seriously injured older adults, but research is sparse. We evaluated the utility of comorbidities, anticoagulant use, and geriatric-specific physiologic measures to improve the sensitivity of the field triage guidelines for high-risk older adults in the out-of-hospital setting. METHODS: This was a cohort study of injured adults 65 years or older transported by 44 emergency medical services agencies to 51 trauma and nontrauma hospitals in seven Oregon and Washington counties from January 1, 2011, to December 31, 2011. Out-of-hospital predictors included current field triage criteria, 13 comorbidities, preinjury anticoagulant use, and previously developed geriatric specific physiologic measures. The primary outcome (high-risk patients) was Injury Severity Score of 16 or greater or need for major nonorthopedic surgical intervention. We used binary recursive partitioning to develop a clinical decision rule with a target sensitivity of 95% or greater. RESULTS: There were 5, 021 older adults, of which 320 (6.4%) had Injury Severity Score of 16 or greater or required major nonorthopedic surgery. Of the 2, 639 patients with preinjury medication history available, 400 (15.2%) were taking an anticoagulant. Current field triage practices were 36.6% sensitive (95% confidence interval [CI], 31.2%–42.0%) and 90.1% specific (95% CI, 89.2%–91.0%) for high-risk patients. Recursive partitioning identified (in order): any current field triage criteria, Glasgow Coma Scale score of 14 or less, geriatric-specific vital signs, and comorbidity count of 2 or more. Anticoagulant use was not identified as a predictor variable. The new criteria were 90.3% sensitive (95% CI, 86.8%–93.7%) and 17.0% specific (95% CI, 15.8%–18.1%). CONCLUSIONS: The current field triage guidelines have poor sensitivity for high-risk older adults. Adding comorbidity information and geriatric-specific physiologic measures improved sensitivity, with a decrement in specificity. LEVEL OF EVIDENCE: Prognostic/Epidemiologic, level II.